The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/humupd/dmv039
|View full text |Cite
|
Sign up to set email alerts
|

What we know about primary dysmenorrhea today: a critical review

Abstract: Further study is needed to determine whether effectively blocking dysmenorrheic pain ameliorates risk for the development of chronic pain disorders and to explore whether it is possible to prevent the development-and not just treat-severe dysmenorrheic pain in adolescent girls. In conclusion, we demonstrate the extensive multi-factorial impact of dysmenorrhea and we encourage and direct researchers to necessary future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
749
2
94

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(866 citation statements)
references
References 208 publications
21
749
2
94
Order By: Relevance
“…In agreement with our result, it was found that dysmenorrheic women had more disturbed sleep and subjective sleepiness than controls. Their sleep efficiency was reduced when experiencing menstrual pain, with increased wakefulness, movement [30].…”
Section: Socio-demographic and Gynaecological Data Dysmenorrhea N = 1mentioning
confidence: 99%
“…In agreement with our result, it was found that dysmenorrheic women had more disturbed sleep and subjective sleepiness than controls. Their sleep efficiency was reduced when experiencing menstrual pain, with increased wakefulness, movement [30].…”
Section: Socio-demographic and Gynaecological Data Dysmenorrhea N = 1mentioning
confidence: 99%
“…Other chronic pain disorders that involved tissue damage or systemic symptoms, such as chronic low back pain (CLBP) and fibromyalgia, might suffer from constant peripheral nociceptive feedbacks [122] and are thus more likely to show systemic and rhythmic changes in central nervous system that can be captured by linear analyses, such as spectral analysis. Second, although PDMs do suffer from significant negative cognitive and emotional consequences when compared to healthy females including depression, anxiety [7,11], they are considered as otherwise-healthy females who do not suffer from cognitive impairments or mental dysfunctions. This is reasonable to consider that local linear synchrony neural activities in PDMs are similar to those in CONs when spontaneous pain (menstrual pain) does not exist.…”
Section: Mse Versus Spectral Analysesmentioning
confidence: 99%
“…It is a worldwide public health problem associated with mildly increased mortality [4]. Primary dysmenorrhea (PDM), highly prevalent yet undertreated and affecting 40-90% of the reproductive-age females [5][6][7], is a pelvic pain during menstruation without identifiable structural lesion or anomaly in the internal female genital organs [8]. PDM is a good clinical model for studying chronic pain because of its natural "on" (painful) and "off" (pain-free) states.…”
Section: Introductionmentioning
confidence: 99%
“…Результаты проведен-ного нами скринига показали аналогичную частоту встре-чаемости данного синдрома в исследуемой популя-ции -20%, при этом более тяжелые его формы, приводя-щие к существенному снижению КЖ, встретились с часто-той 7,5%. Кроме того, влияющие на КЖ обильные менстру-альные кровотечения составляют 10,9% [25], дисмено-рея -45% [26], нерегулярный менструальный цикл -10-30% [27]. Эти данные также совпадают с полученными нами результатами.…”
Section: обсуждение результатовunclassified